Subclinical hypothyroidism would not lead to female sexual dysfunction in Chinese women - Han Luo; Wanjun Zhao; Hongliu Yang; Qianqian Han; Li Zeng; Huairong Tang; Jingqiang Zhu (BMC, 2018)
Abstract Background There is dearth of research about female sexual dysfunction (FSD), especially in China, because of conservative beliefs. Previous studies indicated the relationship between subclinical hypothyroidism and anxiety and depression. However, there is dearth of research regarding the relationship between subclinical hypothyroidism and FSD in Chinses women. Method A hospital-based research was conducted. Female sexual function was measured by CVFSFI which includes 19 items. Participants were identified as FSD if CVFSFI ≤ 23.45. Logistics analysis was used to determine risk factor of FSD. All of them finished CVFSFI, Beck Depression Inventory (BDI) self-reporting questionnaires and had thyroid hormone tests. Based on presence and absence of subclinical hypothyroidism, participants were divided into two groups. Risk factors of FSD were identified. Result One thousand one hundred nineteen participants with CVFSFI score 25.8 ± 3.9 were enrolled in final analysis. Incidence of subclinical hypothyroidism and FSD in Chinese women was 15.0% and 26.5% respectively. There were no significant difference between subclinical hypothyroidism and control group in FSFI score and prevalence of FSD. Age, Depression (medium risk) was identified as risk factors for nearly all types of FSD, and Income (ranges from 40,000 to 100,000 RMB/year) as protective factor. Subclinical hypothyroidism had no significant relationship with FSD. Conclusion Subclinical hypothyroidism is not the risk factor for FSD in urban women of China.